MAGNITUDE: transcranial magnetic stimulation for treatment-resistant Obsessive-Compulsive Disorder: a randomized sham-controlled phase II trial protocol - Rech, Lavinia (2025)
Obsessive–Compulsive Disorder (OCD) is a chronic psychiatric condition with a lifetime prevalence of 2–3%. It significantly burdens quality of life and is associated with substantial economic and disease burdens. Cognitive-behavioral therapy and high-dose selective serotonin reuptake inhibitors are considered the first-line treatments for OCD. Approximately two-thirds of patients with Obsessive–Compulsive Disorder (OCD) exhibit inadequate responses to current standard therapies, thus lacking adequate therapy, resulting in a loss of quality of life and huge economic burdens. Repetitive transcranial stimulation (rTMS) is a non-invasive, safe, and well-tolerated intervention that modulates prefrontal cortical circuits involved in OCD. A previous systematic review explored the therapeutic effects of rTMS applied to the dorsolateral prefrontal cortex (dlPFC) area in patients with treatment-resistant OCD. It showed that the application of high-frequency and low-frequency (LF) rTMS to the dlPFC region yielded controversial post-treatment Y-BOCS (Yale-Brown Obsessive–Compulsive Scale) findings due to factors such as small sample sizes, short-term study durations, and variations in rTMS protocols. Objectives: Thus, we propose a theoretical protocol based on previous findings to assess better the effect of LF rTMS for treatment-resistant OCD patients. Methods: We will recruit patients with moderate to severe OCD and limited response to previous treatments from in- and outpatient clinics. We will use fMRI for precious localization of the right dlPFC and application of 1 Hz stimulation of in total 2000 pulses with three times 40 s inter-train intervals 5 days a week, in 6 consecutive weeks. The primary outcome will be the mean reduction in Y-BOCS at the end of this study. Conclusions: This study highlights rTMS’s potential to reform OCD treatment, accentuate safety, accessibility, clinical integration, and future research foundations.